The Diversion for Children Who are Doing Crime of Theft - Sudarwin Sudarwin (Universitas Ahmad Dahlan, 2020)
Introduction to The Problem: This article is based on the problems related to the handling of children in conflict with the existing law so far that it is still not free from treatments that are oriented towards depriving independence. The deprivation of liberty in question even occurs in cases of theft that actually can be resolved through restorative justice through diversion.Purpose/Objective Study: The aim of this research is to find out how the actual regulation of diversion related to criminal acts of theft in Law No. 11 of 2012 concerning the Juvenile Justice System and other related regulations, and how the implementation of diversion concept, especially against criminal theft.Design/Methodology/Approach: This article uses descriptive normative writing methods, namely explaining the facts related to the implementation of diversion in a criminal act of theft, how the arrangements and author’s suggestions for the diversion arrangement in the future. The source of the data used is secondary data sources, namely, data sources obtained from literature studies, such as books, journals, newspaper articles, and the internet.Findings: There are problems in Law No. 11 of 2012 concerning the Juvenile Justice System, where diversion provisions are limited only to crimes under 7 (seven) years, which have made many child offenders end up in the deprivation of liberty decisions. Then, the provisions of Article 9 Paragraph (2) of the act that eliminates or does not involve victims in diversion efforts whose losses are below the provincial minimum wage have harmed the concept of restorative justice. So, there needs to be some improvement such as the legislation governing diversion should no longer be limited by providing requirements regarding the implementation of diversion based on the number of penalties but the criminal acts that can be regulated by police regulation, and the diversion should be carried out by bringing together perpetrators and victims without exception.Paper Type: Research Article